Sleep deprivation-induced multi-organ injury: role of oxidative stress and inflammation - Periasamy, Srinivasan; Hsu, Dur-Zong; Fu, Yu-Hsuan; Liu, Ming-Yie (Technische Universität Dortmund, 2015)
Sleep deprivation affects all aspects of health. Adverse health effects by sleep deviation are still underestimated and undervalued in clinical practice and, to a much greater extent in monitoring human health. We hypothesized that sleep deprivation-induced mild organ injuries; oxidative stress and inflammation might play a crucial role in inducing multi-organ injury. Male C57BL/6J mice (n = 6-7) were sleep-deprived for 0-72 h using a modified multiple platform boxes method. Blood and tissue were collected. Liver, heart, kidney, lung, and pancreatic injuries were evaluated using biochemical and histological analyses. Glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), total billirubin (TBIL), creatine phosphokinase (CPK), creatine phosphokinase-myocardial band (CKMB), lactic dehydrogenase (LDH), creatinine (CRE), and blood urea nitrogen (BUN) were assayed in blood. Malondialdehyde (MDA), nitric oxide (NO), tumor necrosis factor (TNF)-ɑ, interleukin (IL)-1β, and IL-6 levels were measured. Histology revealed mild-to-moderate liver and lung injury in sleep-deprived mice. Sleep-deprived mice had significantly higher GOT, GPT, TBIL, CPK, CKMB, LDH, BUN, and ɑ-amylase (AMYL) levels, which indicated liver, heart, kidney, and pancreatic injuries. Serum IL-1β at 24 h and IL-6 at 72 h were significantly higher in sleep-deprived than in control mice. Hepatic TNF-ɑ and IL-1β were significantly higher, but IL-6 significantly lower in mice that had been sleep-deprived for 72 h. Sleep deprivation-mediated inflammation may be associated with mild to moderate multi-organ damage in mice. The implication of this study indicates sleep deprivation in humans may induce multi-organ injury that negatively affects cardiovascular and gastrointestinal health.
EXCLI Journal;Vol. 14, 2015
Keywords: sleep deprivation; multi-organ injury; inflammation; oxidative stress; 610